Frühneuhochdeutsche Neuerungen im Spiegel der Schreibung der Krakauer Stadtkanzlei - Piotr A. Owsiński (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The article hereunder presents the language analysis of chosen medieval charters from 14th century taken from the “Antiquum Registrum Privilegiorum Et Statutorum Civitatis Cracoviensis” published by Stanisław Estreicher in 1936 in Cracow. The texts of the unknown scriveners were written in Early New High German in the Silesian dialect, what can be proved on the basis of legal annotations. The author introduces the results of his analysis showing the Early New High German characteristic features illustrated by appropriate examples.